Alih Pengetahuan Desain Kemasan dan Komunikasi Pemasaran Digital pada Pelaku UMKM Pantura Oleh-oleh Pulau Seribu di Pulau Panggang - Alessandro Kurniawan Ulung; Rustono Farady Marta; Sri Rachmawati H Siregar (Institut Keuangan-Perbankan Dan Informatika Asia Perbanas, 2026)
This community service program aims to enhance the capacity of small and medium enterprises (UMKM) Pantura Oleh-Oleh Pulau Seribu in Pulau Panggang, Kepulauan Seribu, Jakarta, through targeted training on packaging design and digital marketing communication. These initiatives expect to strengthen the role of UMKM Pantura as a non-state actor in supporting the paradiplomacy efforts of the Jakarta Government, particularly in advancing Sister City partnerships. The training sessions were implemented on August 5 and 6, 2025, in Pulau Panggang. The program employed an educative–participative approach, integrating outreach activities and technical assistance for UMKM, supplemented by field surveys, interviews, and in-depth observation. This approach facilitated active engagement and contextual understanding of the challenges faced by local enterprises. This community service contributed to improving UMKM Pantura’s comprehension of packaging design and digital marketing communication. This initiative underscores the importance of empowering UMKM to enhance the effectiveness of paradiplomacy conducted by municipal governments.